Protein minimum requirements from some vegetable sources for laboratory growing rats - Oliveira, Ida Maria Vianna de; Angelis, Rebeca Carlota de (Brazilian Journal of Veterinary Research and Animal Science, 2001)
The protein minimum requirement for maintenance of body weight and nitrogen from growing rats was determined by protein utilization of some vegetable sources in relation to casein and by evaluation of some biochemical indicators (plasma protein and albumin, liver protein). Weanling Wistar rats were fed on experimental diets (3%, 5% or 7% rice; 6%, 8% or 10% bean; 4%, 6% or 8% rice-and-bean) and control diets (3%, 5%, 7% or 28% casein and free protein diet) during 28 days (50 days of age). The estimated minimal requirements of protein seems to be dependent on protein quality and were 3.6%; 7.4%; 4.9% and 3.7% respectively to rice, bean, rice-and-bean and casein. The biochemical parameters were significantly reduced in experimental groups when compared to casein 7% and 28% controls. The results obtained could suggest a metabolic adaptation to protein restriction and a possibility to overcome the poor protein quality by increasing the dietary protein quantity.